Pengaruh Mesh Size Jaring Insang Dasar (Bottom Gill Net) terhadap Hasil Tangkapan Ikan Kakap Merah (Lutjanus spp.) dengan Ukuran di Atas 300 Gram di Perairan Teluk Ekas, Lombok Timur - Mokhammad Ravil Faisal Amir; Exist Saraswati; M. Tajuddin Noor (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2025)
Ekas Bay has very rich fishing potential, especially for the red snapper species (Lutjanus spp.). This study aims to determine the effect of mesh size of gill nets on catch and determine the mesh size that is more effective for catching Red Snapper (Lutjanus spp.) measures above 300 grams in the waters of Ekas Bay, East Lombok. This research was carried out in the waters of Ekas Bay, East Lombok from June to August 2025. This research method uses an experimental method that distinguishes three treatments with nine replications, using a Group Random Design (RAK). The data collection techniques in this study are observation, active participation, and interviews. Then analyzed using multiple fingerprint analysis (ANOVA). If the effect is real or very real, the effect can be seen by using the smallest real difference test (BNT), after that the BNT value is compared to the average value of the treatment. The results of the study showed that the use of different mesh sizes had a very real effect on the catch of red snapper. The 4-inch mesh proved to be the most effective with 65% of the fish caught being ≥300 grams in size, while the 3-inch mesh was 30% and the 2-inch mesh was only 5%. Thus, the use of larger mesh can increase selectivity for adult fish while reducing juvenile catches.